Selective fatty replacement of the exocrine pancreas in a domestic shorthair cat: histopathological findings with long-term outcome - Melanie J Dobromylskyj; Peter Dobromylskyj (Journal of Feline Medicine and Surgery Open Reports, 2015)
The clinical, histopathological findings and eventual outcome of a cat with marked and selective fatty replacement of the exocrine pancreas are described in this case report. A 9-year-old female neutered domestic shorthair cat presenting with polyphagia, weight loss and intermittent vomiting was diagnosed on histopathology with severe exocrine pancreatic atrophy, with relative sparing of the endocrine pancreas and replacement of the acinar cells by mature adipose tissue. This case report discusses the histological findings in this case and the eventual outcome, as well as the potential underlying causes of this histological change.